(Im)Proving It: Designing a Measurement System that Nourishes Innovation. (December 2013) - Jenkins, Julian; Golsby‐Smith, Tony
<x xml:space="preserve">Abstract</x> Use of the business‐case method to assess the viability of a new business model or an untried product category emphasizes avoiding financial risks—but forgets to consider the risk of not innovating. These authors offer instead some key principles and a methodology for measuring the performance of an innovative project. The business‐case method of proving the efficacy of design thinking is a losing proposition.